Exploring Feedback Mechanisms in Higher Educational Governance: Learning from a Case Study (Contemporary Research: An Interdisciplinary Academic Journal, 2024)
Feedback mechanisms are critical elements of an institution's educational governance. This paper aims to explore the role of feedback mechanisms in the context of educational governance within the higher education system on campus. Utilizing a descriptive research design that incorporates a case study approach, the researchers identified four faculty members, and three non-teaching staff members as key informants, through purposive sampling. Additionally, 50 students from various programs across the three faculties and 42 corresponding guardians were selected as respondents using a random sampling method. Questionnaires, interview schedules, and non-participant observation forms were the basic tools for data collection. The researchers employed program theory as a theoretical framework. The research underscores the essential function of constructive feedback in improving educational results and emphasizes the necessity of incorporating stakeholder viewpoints into governance frameworks. A lack of a strong and effective feedback system is apparent in the educational governance at campus, particularly in relation to curriculum design, teaching methods, assessment systems, and services. This paper posits that feedback mechanisms are fundamental to ensuring quality education within the institution. It is imperative for campus administration to actively oversee and deliver feedback to the relevant educators, rather than solely to the teaching staff and students.